2013
DOI: 10.5222/jopp.2013.131
|View full text |Cite
|
Sign up to set email alerts
|

Should Children with Minor Head Injury Routinely Have CT Scan?

Abstract: Minör kafa travması acil servise çocukların en sık başvurma nedenlerindendir. Bilgisayarlı tomografi (BT) çocuklarda travmatik beyin yaralanması yönetiminde sık kullanılır. Bu çalışmanın amacı minör kafa travmasında BT yararlılığını sunmaktı.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Patients with minor head trauma constitute 83% of the present study group and the demographic CT -Computed Tomography distribution of patients in this group is compatible with the literature [9][10][11]. In the study of Guneş et al [10], 58% of the patients were male and 80.3% were above 2 years old, while these results were found 60.1% and 83.3% in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Patients with minor head trauma constitute 83% of the present study group and the demographic CT -Computed Tomography distribution of patients in this group is compatible with the literature [9][10][11]. In the study of Guneş et al [10], 58% of the patients were male and 80.3% were above 2 years old, while these results were found 60.1% and 83.3% in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Skull fractures constituted most of the pathologies seen in trauma patients (80%) in this study, following the literature. This rate was found to be 82% in the study of Guneş et al [10], and 57.8% in the study of Er et al [9]. In the study of Kuppermann et al, it was reported that most of the patients with head trauma admitted to the ED were patients with mild head trauma, and traumatic brain injury was detected in less than 10% of these patients, which is similar to the present study [12].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Paediatric head injuries are still important today. It is one of the highest causes of mortality and morbidity in paediatric traumas and seen commonly despite the use of special facilities with developing technologies for children such as special playgrounds, protective equipment against potential domicile accidents, and child safety seats providing the least damage during a traffic accident [1,2]. Especially, in underdeveloped and developing countries, traumas are among the leading causes of death among the young population and more than half of these deaths result from head traumas [3].…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography (CT) is recommended as the first imaging method to be performed in patients with severe head injuries without discrimination of children or adults [1]. In minor head traumas, it is recommended only in the selected patient group due to its cost and high dose radiation exposure [2,7]. In the group of patients with minor head trauma, the rate of detection of pathological findings in cranial CT is between 4-8%, and only a small part of these pathologies results in mortality.…”
Section: Introductionmentioning
confidence: 99%